Análisis del proceso de afiliación en el IESS - Los Ríos - Barreiro Mora, Gregory Kelvin (2021)
This research is focused on carrying out an analysis of the affiliation process in the Ecuadorian Social Security Institute (IESS) - Los Ríos, it is intended to identify the factors that do not allow the early affiliation of workers and the problems that arise within this Department; Qualitative research was used that tries to collect non-numerical information; A descriptive study was also used to describe the characteristics of the population to be studied. The research methods used were the bibliographic with which I was able to find the existing theories, the inductive method and the scientific method that is in general use in research, the information collection technique that was applied was the survey by means of a questionnaire, with which it was possible to obtain the primary information necessary to develop the present case study. The sub-line of research is that of the trade degree "Public and private companies and institutions".